A study of the strain signals behaviour - Ng, Jun Pin (2013)
This study presents the study of strain signals behavior. In this study, the strain signal of helical spring at different value of excitations is used to study the signals behavior. When a vehicle was driven on any road surfaces, the significant load is transmitted to the helical spring to absorb loads. The load values were varied according to the type of the road surfaces. The signals were analyzed by statistical analysis and frequency-time domain. Signals are classified based on the value of the statistical parameter. The signals are used to predict fatigue damage of the helical spring. From the result obtained, the unpaved road signals consist of higher peak shocks. It exhibited higher statistical value compared to the signals obtained from university road and highway. These feature increased the fatigue damage potential of the helical spring. The finite element analysis of helical spring was performed by MSC Nastran with Patran software. The finite element model was analysed using the linear elastic stress. Finally, the result obtained and signals are employed to test the fatigue damage of helical spring. Strain-life model which are Coffin-Manson, SWT and Morrow model are used to predict the fatigue damage of helical spring. The obtained result indicated that unpaved road has the highest fatigue damage followed by university road and highway.